Complications of traditional circumcision amongst young Xhosa males seen at St Lucy's Hospital, Tsolo, Eastern Cape, South Africa - Ugochukwu Anike; Indiran Govender; John V. Ndimade; John Tumbo (AOSIS, 2013)
Background: Traditional circumcision of males is common amongst many societies in sub-Saharan Africa. Circumcision amongst the Xhosa people of South Africa represents a rite of passage to manhood. Traditional male circumcision has an increased risk for complications that include sepsis, genitalmutilation, gangrenous penis, excessive bleeding, dehydration, renal failure and death. The aim of this study was to describe the complications of traditional circumcisions amongst Xhosa men as seen at St. Lucy's Hospital in the Eastern Cape Province. Method: A cross-sectional descriptive quantitative study was conducted in 2008. Records of 105 malesadmitted to St. Lucy's Hospital with complications following traditional circumcision were reviewed. Data collected included age, education level, race, reasons for circumcision, complications, the period of circumcision, duration of hospital stay and the outcomes. Descriptive data analysis was performed using statistical software SPSS 17.0. Results: The ages ranged from 15-35 years with 68 (64.8%) between 15-19 years. 83 (79%) had a secondarylevel of education, 16 (15.2%) primary, 5 (4.8%) tertiary and 1% had no education. 60 (57%) werecircumcised as initiation to manhood, 21 (20.0%) due to peer pressure, 20 (19.0%) for cultural reasons, and 1(1.0%) was forced. The complications were sepsis (59 [56.2%]), genital mutilation (28 [26.7%]), dehydration(12 [11.4%]) and amputation of genitalia (6 [5.7%]).Fifty-nine (56.2%) patients were circumcised in winter.79 (75.2%) were circumcised in the forest, and 25 (23.8%) in initiation centres. Fifty-eight (55.2%) werecircumcised by traditionalists, and 47 (44.8%) by tribal elders (initiators). Hospital stays ranged from 8 to28 days. 66% were healed and discharged, and 29 (27.6%) were referred to higher centres of care. Conclusion: Genital sepsis was the most common complication of traditional male circumcision.Complications were related to the circumciser, advanced age of the patient and place of circumcision. Thereis need for training of the traditional circumcisers on safe techniques and use of hygienic practices in orderto reduce the complications identified in this study.